Treatment of anoestrus local Iraqi buffaloes (Bubalus bubalis) using different hormones - field study: Haddawi M.Dahham1@,Abbas H.N. Aal-Saied, W.S. Saied and Hassan A. H. Al-Tamimy2 - Dahham, Haddawi M. (The Iraqi Journal of Veterinary Medicine, 2014)
This study aimed to evaluate the efficacy of different hormonal treatments protocols (PGF2α ,GnRH, estradiol and progesterone) hormones on reproductive performance of postpartum anoestrus native dairy River buffaloes (Bubalus bubalis), endemic south of Baghdad under field conditions . Present study was conducted on 128 animals that had postpartum anoestrus (PPA) for a period between 4 to 8 months. The animals were subjected to two experiments according to the type of anoestrus. In the first experiment 94 animals (73.5%) with persistent corpus luteum on their ovaries without any signs of estrous (sub-oestrus) were classified into two sub-groups.Sub-group1 (n=47) treated with PGF2α hormone alone and sub-group 2 (n= 47) were treated by two injections. The first injection was PGF2α. while the second injection GnRH+ PGF2α was injected after 9 days.In second experiment 34 buffalo cows without any structure on their ovaries (True anestrous) were classified into two sub-groups according to design of the treatment. Sub-group 1(n=14) was treated with estradiol as single injection. Sub-Group 2(n=20) received estradiol + progesterone .The results indicated that the pregnancy rate in sub- groups1 and 2 of the first experiment were 85.1% and 89% respectively , which was not significantly differ from each other (P < 0.05). While in the second experiment, the pregnancy rate for the first and second sub- groups were 71% and 75%, respectively. This study concluded that the prevailing situation of anestrous in postpartum buffaloes endemic south of Baghdad is anestrous with corpus luteum (Sub-oestrus) , 94 out of 128 (73.5%) , and the most efficient treatment protocol of these case are PGF2α + GnRH hormones ( pregnancy rate= 89%) . While estradiol + progesterone treatment are efficient in the treatment of animals suffering from true anestrous (pregnancy rate 75%).